Measuring readiness for and satisfaction with a hand hygiene e-learning course among healthcare workers in a paediatric oncology centre in Guatemala City - Gonzalez, Miriam Lourdes; Melgar, Mario; Homsi, Maysam; Shuler, Ana; Antillon-Klussmann, Federico; Matheu, Laura; Ramirez, Marylin; Grant, Michael M; Lowther, Deborah L; Relyea, George; et al. (International Journal of Infection Control, 2016)
E-learning has been widely used in the infection control field and has been recommended for use in hand hygiene (HH) programs by the World Health Organization. Such strategies are effective and efficient for infection control, but factors such as learner readiness for this method should be determined to assure feasibility and suitability in low- to middle-income countries. We developed a tailored, e-learning, Spanish-language HH course based on the WHO guidelines for HH in healthcare settings for the paediatric cancer centre in Guatemala City. We aimed to identify e-readiness factors that influenced HH course completion and evaluate HCWs’ satisfaction. Pearson’s chi-square test of independence was used to retrospectively compare e-readiness factors and course-completion status (completed, non-completed, and never-started). We surveyed 194 HCWs for e-readiness; 116 HCWs self-enrolled in the HH course, and 55 responded to the satisfaction survey. Most e-readiness factors were statistically significant between course-completion groups. Moreover, students were significantly more likely to complete the course if they had a computer with an Internet connection (P=0.001) and self-reported comfort with using a computer several times a week (p=0.001) and communicating through online technologies (p=0.001). Previous online course experience was not a significant factor (p=0.819). E-readiness score averages varied among HCWs, and mean scores for all e-readiness factors were significantly higher among medical doctors than among nurses. Nearly all respondents to the satisfaction survey agreed that e-learning was as effective as the traditional teaching method. Evaluating HCWs’ e-readiness is essential while integrating technologies into educational programs in low- to middle-income countries.